Credit Analysis at the Regional Office of the Director General of State Treasury for Bangka Belitung Province - Febriyani, Lintri; Nugroho, Ari Agung; Leksono, Binar Kukuh (Garuda Prestasi Nusantara Consulting, 2023)
The MSME sector (Micro, Small and Medium Enterprises) is one of the backbones of the Indonesian economy. But its existence is still experiencing various obstacles. The government is present to provide support for the MSME program through the allocation of the APBN (State Revenue and Expenditure Budget) and APBD (Regional Revenue and Expenditure Budget). In the 2022 State Budget, the Province of Kep. Bangka Belitung received an allocation of IDR 13.47 billion for the Economic Recovery cluster. Meanwhile, the APBD allocation is IDR 8.19 billion, divided into two programs, namely MSME Empowerment and MSME Development worth IDR 6.5 billion and IDR 1.69 billion. The results of the 2022 credit analysis at the Regional Office of the Director General of Treasury of the Bangka Belitung Province in order to increase MSME empowerment found that the characteristics of MSMEs in the Kep Province area. Bangka Belitung is dominated by micro-scale businesses, reaching 97.96 percent or 186,101 business actors. Bangka Belitung MSMEs have not fully optimized financing facilities. The achievement of MSME financing is lower than non-MSMEs financing. MSME actors in 2022 will only access financing with a total credit of IDR 6 trillion from the total credit ceiling of commercial banks of IDR 14.3 trillion. Even the proportion of KUR/UMi debtors to Bangka Belitung MSMEs is only 21.68 percent.